Accurate diagnosis of bronchopulmonary Talaromyces marneffei infection in an anti-IFN-γ autoantibodies positive patient assisted by endobronchial ultrasound-guided TBNA and mNGS: a case report - Chen, Guirong; Ma, Nan; Zhu, Donglan; Zhou, Huaihai; Liang, Qiumei; Meng, Jianfeng; Shen, Yin; Liu, Hang; Liu, Liu; He, Zhiyi; Qin, Zhiqiang (Frontiers in Cellular and Infection Microbiology, 2023)
Rationale: T. marneffei is opportunistic and dimorphic fungus, which can cause systemic mycosis in human beings. It’s being difficult to obtain histopathological or microbiological evidence in T. marneffei infection. We reported a rare non-HIV case of T. marneffei infection of bronchopulmonary and mediastinal lymph nodes which was diagnosed by EBUS-TBNA combined with mNGS. The high titer of anti-IFN-γ autoantibodies in serum was probably the cause of T. marneffei infection,which has yet to be fully known. Patient concerns: A 56-year-old Chinese man presented with a 5-month history of intermittent low or high fever and dry cough, followed by fatigue, night sweating, and chest pain when coughing. A large hilar lesion in the left lung and multiple mediastinal lymph node enlargements were found on his chest CT scan. Diagnoses: The patient received EBUS-TBNA of hilar tissue and lymph node biopsy for mNGS at the second Ultrasonic bronchoscopy. No fungal hyphae or spores were found in the histopathology. There were high sequencing reads of T. marneffei in samples of lymph node fluid and bronchogenesis tissue detected by mNGS. His plasma anti-IFN-γ autoantibodies level was positive with a high titer at 1:2500↑. Intervention: The patient went through atrial fibrillation at the first dose of amphotericin B liposomes and treated with voriconazole later. Outcomes: His fever, cough and dyspnea quickly disappeared since the fourth day of treatment. After six months, there was not any focus in his chest CT scans. But his plasma anti-IFN-γ autoantibodies remained unchanged. Lessons: Complementing the traditional laboratory and bronchoscopy, mNGS combined with EBUS-TBNA facilitate rapid and precise diagnosis of bronchopulmonary mediastinal lymph nodes T. marneffei infection. Clinicians should be aware of anti-INF-γ autoantibodies in opportunistic infections of non-HIV patients.